Implementation of Tradeable Permit Instruments in Water Resource Utilization in Makassar City - Hanafie, Nurharsya Khaer; Muhtar, Muhtar; Satrul, Hairul Saleh (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study aims to analyze the potential and challenges of implementing tradeable permits in the management and utilization of water resources in Makassar City. The background of this study is driven by increasing pressure on water resources due to population growth, industrial expansion, and changes in land use. The command and control approach that has been applied through water extraction and utilization permits has not been able to promote efficiency and fairness in the distribution of water resources. Therefore, policy innovation based on environmental economic instruments is needed. The research method used a legal-empirical approach, with analysis of national and regional legislation related to water resource management, as well as in-depth interviews with the Makassar Public Works and Spatial Planning Agency (PUPR), Makassar Water Company (PDAM), and industry players. The results of the study show that the implementation of tradeable permits has the potential to increase the efficiency of water allocation between sectors and encourage water resource conservation. However, challenges arise in terms of institutional aspects, monitoring mechanisms, and the readiness of quantitative data systems related to water utilization quotas. This study concludes that the implementation of tradeable permits for water resources in Makassar could be a progressive policy alternative, but it requires a clear operational legal basis, an integrated monitoring system, and cross-sector coordination between local government, PDAM, and business actors.